Bio-milling technique for the size reduction of chemically synthesized BiMnO3 nanoplates - Mazumder, Baishakhi; Uddin, Imran; Khan, Shadab; Ravi, Venkat; Selvraj, Kaliaperumal; Poddar, Pankaj; Ahmad, Absar (Journal of Materials Chemistry, 2007)
Wet- chemical techniques for the synthesis of complex oxide materials have advanced significantly; however, achieving finely dispersed nanoparticles with sizes less than 10 nm still remains challenging, especially for the perovskite family of compounds. On the other hand, a fungusmediated synthesis technique has recently shown potential to synthesize perovskites such as BaTiO3 with sizes as small as 5 nm. Here we report, for the first time, the use of fungal biomass, at room temperature, to break down chemically synthesized BiMnO3 nanoplates ( size similar to 150 - 200 nm) into very small particles (, 10 nm) while maintaining their crystalline structure and the phase purity. This novel technique that we have named as `` bio- milling'' holds immense potential for synergically utilizing both chemical and biological synthesis techniques to synthesize complex oxide nanoparticles with particle sizes less than 10 nm with the proper crystalline phase.

Structure and microbial synthesis of sub-10 nm Bi2O3 nanocrystals - Uddin, Imran; Adyanthaya, Suguna D.; Syed, Asad; Selvaraj, K.; Ahmad, Absar; Poddar, Pankaj (Journal of Nanoscience and Nanotechnology, 2008)
After the advent of novel chemical and microbial techniques, providing control over grain size and shape of the nanomaterials, several binary-oxide materials have been explored in size less than 10 nm for their tunable physical properties. Bi2O3 nanoparticles have also redrawn attention due to their excellent properties, mostly as optoelectronic material. Here, we report the room-temperature biosynthesis of Bi2O3 nanoparticles in a size range of 5-8 nm by extra-cellularly challenging the plant pathogenic fungus-Fusarium oxysporum with the bismuth nitrate as precursor. The as-synthesized particle-surfaces are inherently functionalized by a robust layer of proteins which provides them very good stability in the aqueous medium. Structural investigation using selected area electron diffraction, high resolution transmission electron microscopy and powder XRD shows that particles are almost perfectly single crystalline and primarily crystallize in alpha-phase with monoclinic structure.
Keywords: Biosynthesis; fungi; High Refractive Index; High Resolution TEM; Nanoparticles

Extracellular biosynthesis of water dispersible, protein capped Mn5O8 nanoparticles using the fungus fusarium oxysporum and study of their magnetic behavior - Uddin, Imran; Poddar, Pankaj (Journal of Nanoengineering and Nanomanufacturing, 2013)
Nanomaterials of different sizes, shapes and compositions are being synthesized by various chemical, physical and biological routes. The pressing need of the hour is to have a synthesis protocol which does not harm the environment in any way and is inexpensive so that the benefits can be reaped by all. In this regard, the biological synthesis routes weigh over the chemical and physical ones which are toxic and expensive respectively. The biological routes occur at ambient conditions of temperature, pressure and pH and help protect the ecosystem as these do not employ any hazardous chemicals. Moreover, the nanoparticles obtained via biological routes are naturally protein capped which prevents their agglomeration and helps them retain their shape, size and stability for several months. One such important material is manganese oxide (Mn5O8) which at the nanoscale, has found good use in catalysis and as ionic conductors in fuel cells or batteries. The compound Mn5O8 exists in mixed valences of Mn2+ and Mn4+ and has drawn attention due to its antiferromagnetic nature. Here we report extracellular biosynthesis of manganese oxide (Mn5O8 nanoparticles in the size range of 10–11 nm at room temperature by challenging the fungus Fusarium oxysporum with manganese (II) acetate tetrahydrate [(CH3CO2)2 Mn · 4H2O] as precursor. The Mn5O8 nanoparticles so formed were characterized by TEM, XRD, FTIR, XPS, and TGA. Two mixed manganese ion valencies (Mn2+ and Mn4+) of Mn5O8 have been confirmed by XPS studies and antiferromagnetic transitions by magnetic measurements.

Novel green bio-milling technique for the synthesis of BaTiO3 nanoparticle using Saccharomyces cerevisiae - Uddin, Imran; Jaiswal, Adhish; Poddar, Pankaj (International Journal of Innovative Biological Research, 2013)
The development of a novel green top-down approach called bio-milling for synthesizing the oxide nanomaterials is an issue of topical interest. While a number of chemical processes are energy intensive and involve toxic chemicals. Here we report, at room temperature, bio-milling of chemically synthesized barium titinate (BaTiO3) particles by challenging the fungus Saccharomyces cerevisiae against aqueous solution of BaTiO3 to synthesize the biogenic nanoparticles. The extracellular breaking of microscaled BaTiO3 particles by extracellular biomolecules/proteins secreted by the fungus under stressed condition results in the formation of particles in nanoregime. XRD spectra and TEM analysis showed that BaTiO3 particles reduce to their size during the interaction with the fungus Saccharomyces cerevisiae and maintaining their phase and crystallinity after bio-milling process.

Fungus-mediated preferential bioleaching of waste material such as fly - ash as a means of producing extracellular, protein capped, fluorescent and water soluble silica nanoparticles - Khan, Shadab Ali; Uddin, Imran; Moeez, Sana; Ahmad, Absar (PLoS One, 2014)
In this paper, we for the first time show the ability of the mesophilic fungus Fusarium oxysporum in the bioleaching of waste material such as Fly-ash for the extracellular production of highly crystalline and highly stable, protein capped, fluorescent and water soluble silica nanoparticles at ambient conditions. When the fungus Fusarium oxysporum is exposed to Fly-ash, it is capable of selectively leaching out silica nanoparticles of quasi-spherical morphology within 24 h of reaction. These silica nanoparticles have been completely characterized by UV-vis spectroscopy, Photoluminescence (PL), Transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and Energy dispersive analysis of Xrays (EDAX).

Biosynthesis of fluorescent Bi2S3 nanoparticles and their application as dual-functionSPECT-CT probe for animal imaging - Uddin, Imran; Ahmad, Absar; Siddiqui, Ejaz Ahmad; Rahaman, Sk. Hasanur; Gambhir, Sanjay (Current Topics In Medicinal Chemistry, 2016)
Bismuth sulphide (Bi2S3) is an excellent semiconductor and its nanoparticles have numerous significant applications including photovoltaic materials, photodiode arrays, bio-imaging, etc. Nevertheless, these nanoparticles when fabricated by chemical and physical routes tend to easily aggregate in colloidal solutions, are eco-unfriendly, cumbrous and very broad in size distribution. The aim of the present manuscript was to ecologically fabricate water dispersible, safe and stable Bi2S3 nanoparticles such that these may find use in animal imaging, diagnostics, cell labeling and other biomedical applications. Herein, we for the first time have biosynthesized highly fluorescent, natural protein capped Bi2S3 nanoparticles by subjecting the fungus Fusarium oxysporum to bismuth nitrate pentahydrate [Bi(NO3)(3).5H(2)O] alongwith sodium sulphite (Na2SO3) as precursor salts under ambient conditions of temperature, pressure and pH. The nanoparticles were completely characterized using recognized standard techniques. These natural protein capped Bi2S3 nanoparticles are quasi-spherical in shape with an average particle size of 15 nm, maintain long term stability and show semiconductor behavior having blue shift with a band gap of 3.04 eV. Semiconductor nanocrystals are fundamentally much more fluorescent than the toxic fluorescent chemical compounds (fluorophores) which are presently largely employed in imaging, immunohistochemistry, biochemistry, etc. Biologically fabricated fluorescent nanoparticles may replace organic fluorophores and aid in rapid development of biomedical nanotechnology. Thus, biodistribution study of the so-formed Bi2S3 nanoparticles in male Sprague Dawley rats was done by radiolabelling with Technitium-99m (Tc-99m) and clearance time from blood was calculated. The nanoparticles were then employed in SPECT-CT probe for animal imaging where these imparted iodine equivalent contrast.

Physicochemical and antimicrobial photodynamic chemotherapy of unsymmetrical indium phthalocyanines alone or in the presence of magnetic nanoparticles - Osifeko, Olawale L.; Uddin, Imran; Mashazi, Philani N.; Nyokong, Tebello (New Journal of Chemistry, 2016)
An AB(3) type photosensitiser, consisting of 4-pyridylsulfanyl units (denoted as B-3) and one aminophenoxy (denoted as A) group (complex 3) was synthesized. Complex 3 was then quaternized to form complex 4. The aminophenoxy substituent of complex 3 was used for the formation of the amide linkage with the carboxylic functionalised magnetic nanoparticles. Complexes 3 and 4 and their conjugates with magnetic nanoparticles were then used for photodynamic antimicrobial chemotherapy on E. coli. The cationic photosensitiser 4 showed a high efficiency for photodynamic antimicrobial chemotherapy at a very low concentration compared to its conjugate on E. coli.

Biomimetic synthesis of CdSe nanoparticles with potential bioimaging applications - Ansary, Abu Ayoobul; Uddin, Imran; Khan, Muhammed I. (International Journal of Pharmaceutical Sciences and Research, 2017)
This study presents in vitro biomimetic synthesis of CdSe nanoparticles using the enzyme, NADPH dependent-Nitrate reductase purified from fungus, Fusarium oxysporum. The synthesis of CdSe nanoparticles was accomplished in the presence of a synthetic peptide having amino acid sequence (γ-Glu-Cys-Glu-Cys)-Gly, which acted as binding molecule. The nanoparticles were synthesized in the size range of 3.9–9.0 nm was analysed using TEM. Further characterization of nanoparticles was done using techniques such as UV, PL, XPS, and FTIR. The as-synthesized CdSe nanoparticles were water dispersible containing free reactive amino groups. These CdSe nanoparticles were conjugated with bi-antennary and tri-antennary glycopeptides opening up the possibilities for their applications in bioimaging. These significant observations will help better understand the mechanism of biosynthesis of fluorescent nanoparticles using fungi. These findings promise an alternative strategy for an eco-friendly, economical, and large-scale synthesis of water dispersible CdSe nanoparticles. These CdSe nanoparticles have promising biomedical-imaging applications without a need for further functionalization.